Analysis of Factors Causing Delays in Inpatient Medical Record Returns at Hospital X - Alfiansyah, Gamasiano; Anindhitya, Lutfi; Nurmawati, Ida; Rahagiyanto, Angga (P3M Politeknik Negeri Jember, 2025)
The delay in the return of inpatient medical records at Hospital X reached 71.23% in February 2022. This indicates a persistently high delay rate that does not comply with the standard for returning inpatient medical records, which is 2 x 24 hours. The purpose of this study was to analyze the factors contributing to the late return of inpatient medical records using the WHO behavior theory. This research employed a qualitative approach, with data collected through interviews, observations, and documentation. The results showed that for the Thoughts and Feelings variable, the contributing factors were the lack of staff knowledge regarding the standard return time for inpatient medical records, as well as the fact that some staff had never attended training or seminars related to medical records. The Personal Reference variable was not identified as a contributing factor. For the Resources variable, there were no supporting facilities available in the medical record return process in each room, the SOPs did not include related units, had not been re-socialized, and were not available in every inpatient room. Regarding the Culture variable, incorrect knowledge was considered correct, and staff had to wait for the doctor’s schedule to complete signature requirements. In conclusion, delays in the return of inpatient medical records were influenced by staff knowledge, training, availability of supporting facilities, incomplete or poorly disseminated SOPs, and habitual practices among hospital personnel during the record return process.